Implementation of Sharia Economy as a Model of Community Empowerment Mosque-Based - Wahab, Abdul; Arsyad, Sulaiman; Syahrani, Risma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The mosque has a very strategic function in the Islamic community both as a place of worship and a media center for holistic development of people. This study describes the function of the mosque as the center of community empowerment activities and the factors that influence it in it. The research method uses qualitative descriptive methods through interviews, field notes, and documentation. The research site is Masjid at-Taqwa Harapan Permai Telagawaru Housing West Lombok. The results showed that Masjid Raya At- Taqwa Housing Harapan Permai Telagawaru West Lombok, represents a mosque that is able to revive the spirit of community empowerment movement in the field of religious spiritual, economic, educational, social, and cultural arts development. The success of mosque-based community empowerment activities in at-Taqwa Mosque is supported by adequate human resources depicted in the organizational structure of the ideal mosque management council and supported by effective communication capabilities of the da'i. This study recommends the importance of professionalism in the management of mosques and the importance of managing effective communication with both congregations and other stakeholders. This research enriches the study of the development of Islamic society, especially in the empowerment of mosque-based communities.